2005
DOI: 10.3748/wjg.v11.i29.4560
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic analysis of esophageal varices in patients with liver cirrhosis using color Doppler ultrasound

Abstract: Hemodynamics of the PV is unrelated to the degree of endoscopic abnormalities in patients with liver cirrhosis. The most important combinations are endoscopic findings followed by the LGV hemodynamics. Duplex-Doppler ultrasonography has no value in the identification of patients with cirrhosis at risk of variceal bleeding. Hemodynamics of the LGV appears to be superior to those of the PV in predicting bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 24 publications
0
44
2
1
Order By: Relevance
“…Previous Doppler ultrasound-based studies have found no signiˆcant diŠerence in V PV among variceal grades (e.g., small vs. large varices or F1 vs. F2 vs. F3 varices). 29,32 We speculate this discrepant nding is due to the diŠerent precision of the 2 measurement modalities. Doppler ultrasound can measure ‰ow in the PV and may be cheaper and more widely available than PC-MRI.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 96%
“…Previous Doppler ultrasound-based studies have found no signiˆcant diŠerence in V PV among variceal grades (e.g., small vs. large varices or F1 vs. F2 vs. F3 varices). 29,32 We speculate this discrepant nding is due to the diŠerent precision of the 2 measurement modalities. Doppler ultrasound can measure ‰ow in the PV and may be cheaper and more widely available than PC-MRI.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 96%
“…It was widely used to explore the relationship between EV hemodynamics associated with portal hypertension and liver cirrhosis [8,9] . Main characteristics of portal hypertension like a decrease in portal flow velocity or an increase in portal vein diameter are detectable by this means [10,11] .…”
Section: Wwwwjgnetcommentioning
confidence: 99%
“…In prior studies it has been suggested that hemodynamics of the left gastric vein appears to be superior to those of the portal vein in predicting patients with cirrhosis who are at a higher risk of bleeding [20]. However, it was not shown that it is superior to portal vein in detecting the presence of esophageal varices.…”
Section: Resultsmentioning
confidence: 82%